Epigenetic underpinnings of the autistic mind: Histone modifications and prefrontal excitation/inhibition imbalance - Fard, Yasaman Arman; Sadeghi, Elham Najjar; Pajoohesh, Zohreh; Gharehdaghi, Zahra; Khatibi, Dorsa Mousavi; Khosravifar, Shaghayegh; Pishkari, Yasamin; Nozari, Shadi; Hijazi, Ahmed; Pakmehr, SeyedAbbas; Shayan, Sepideh Karkon (American journal of medical genetics. Part B, Neuropsychiatric genetics, 2024)
Autism spectrum disorder (ASD) is complex neurobehavioral condition influenced by several cellular and molecular mechanisms that are often concerned with synaptogenesis and synaptic activity. Based on the excitation/inhibition (E/I) imbalance theory, ASD could be the result of disruption in excitatory and inhibitory synaptic transmission across the brain. The prefrontal cortex (PFC) is the chief regulator of executive function and can be affected by altered neuronal excitation and inhibition in the course of ASD. The molecular mechanisms involved in E/I imbalance are subject to epigenetic regulation. In ASD, altered enrichment and spreading of histone H3 and H4 modifications such as the activation‐linked H3K4me2/3, H3K9ac, and H3K27ac, and repression‐linked H3K9me2, H3K27me3, and H4K20me2 in the PFC result in dysregulation of molecules mediating synaptic excitation (ARC, EGR1, mGluR2, mGluR3, GluN2A, and GluN2B) and synaptic inhibition (BSN, EphA7, SLC6A1). Histone modifications are a dynamic component of the epigenetic regulatory elements with a pronounced effect on patterns of gene expression with regards to any biological process. The excitation/inhibition imbalance associated with ASD is based on the excitatory and inhibitory synaptic activity in different regions of the brain, including the PFC, the ultimate outcome of which is highly influenced by transcriptional activity of relevant genes.